Implementasi Kebijakan Tanah Adat Dan Hak-Hak Adat Di Atas Tanah di Provinsi Kalimantan Tengah - Alosios Gorby; Muchlis Hamdi; Deti Mulyati; Romly Arsyad (Universitas Medan Area, 2023)
This research aims to investigate the implementation of policies related to customary land and indigenous rights in Central Kalimantan Province, Indonesia. The research method employed is qualitative analysis involving field surveys, interviews with stakeholders, and analysis of policy-related documents. Theories related to public administration and customary law are used as frameworks for analyzing the policy implementation process. The results of the discussion reveal several challenges in policy implementation, including the mismatch between customary and national laws, land conflicts, and the lack of accurate information provided to indigenous communities. Despite efforts to align policies and improve their implementation, there are still obstacles that need to be addressed to achieve better recognition and protection of customary land and indigenous rights of Dayak indigenous communities in Central Kalimantan Province.